A influência de precursores orgânicos sobre as propriedades estruturais e magnéticas de nanopartículas de CoFe2O4 - Pedra, Pablo Pedreira (2016)
In this work we studied the dependence of two organic precursors, sucrose and glycerin, in the process to obtain CoFe2O4 nanoparticles by co-precipitation method. The samples were studied by different techniques of structural and magnetic characterization. X-ray diffraction Measurements associated with the Rietveld refinement analysis confirm that all samples obtained with and without the addition of organic precursors have a single phase identified in a cubic crystalline system belonging to the space group . The average crystallite size calculated by Scherrer's equation using the full width at half maximum (FWHM) for the samples synthesized without and with concentration of 0.020 mol.L-1 of glycerin and sucrose showed values approximately equal to 14(2), 8(1) and 5(1) nm, respectively. The Williamson-Hall curves show that both organic precursors used in this work influence on the homogeneity of the samples. Transmission electron microscopy analysis indicates that the inclusion of sucrose during the process of synthesis of these materials reduces the average size of the crystallite, it induces a narrowing in the size distribution and change in the particles shape. The X-ray absorption measurements performed in the Co and Fe K-edge of samples synthesized with sucrose and glycerin show a low variation in the density of unoccupied state in the p sublevel however reveal an increase in the interatomic distances between the absorber and the scattering atoms. Magnetization measurements as a function of temperature show a decrease in the blocking temperature (TB) even as a superparamagnetic behavior at room temperature for sample with 0.020 mol.L-1 of sucrose.